1973
DOI: 10.1071/ph730085
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Interstellar Thioformaldehyde

Abstract: The 211 +-212 transition of thioformaldehyde (HCHS) has been observed in absorption in the direction of SagittariusB2. For a rest frequency of 3139· 38 MHz the peak absorption occurs at a radial velocity of 60 ± 4 km s -1. The half-width of the absorption profile is equivalent to 20 kms-1 and the column density of HCHS is greater than 10 16 molecules cm -2. Comparison with the 211 +-212 absorption of formaldehyde (HCHO) at 15 GHz allows the relative abundance of the two molecular species to be computed as a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(41 citation statements)
references
References 0 publications
1
40
0
Order By: Relevance
“…1,2 Few lines of H 2 CS have also been identified in the Orion KL nebula [3][4][5] and in the atmosphere of the comet Hale-Bopp. 6 Laboratory spectroscopic investigations of H 2 CS and its isotopologues have been carried out in the infrared, 7-10 microwave, and millimeter wave ranges.…”
Section: Introductionmentioning
confidence: 96%
“…1,2 Few lines of H 2 CS have also been identified in the Orion KL nebula [3][4][5] and in the atmosphere of the comet Hale-Bopp. 6 Laboratory spectroscopic investigations of H 2 CS and its isotopologues have been carried out in the infrared, 7-10 microwave, and millimeter wave ranges.…”
Section: Introductionmentioning
confidence: 96%
“…The four molecules in this paper (CH 2 CHCN, CH 2 CN, CH 3 CCH, and H 2 CS) were identified in space for the first time towards Sagittarius B2 (Gardner & Winnewisser 1975;Irvine et al 1988;Snyder & Buhl 1973;Sinclair et al 1973) by Article published by EDP Sciences observation of rotational transitions. The microwave spectrum of all these species has been extensively studied in the laboratory so that their spectroscopic properties are accurately known; see a compilation in the JPL and Cologne databases for molecular spectroscopy (Pickett et al 1998;Müller et al 2005).…”
Section: Spectroscopy and Observationsmentioning
confidence: 99%
“…Thioformaldehyde is also found toward the Galactic center, in well-known hot cores such as the Compact Ridge in Orion KL, and in outflows such as those of the Cepheus A star-forming region, where it is a tracer of high-velocity gas (Codella et al 2005) and is either desorbing from grains or rapidly forming in the gas-phase after mantle evaporation. Although an interstellar search for thioformaldehyde was carried out ( Evans et al 1970) soon after the first microwave laboratory study (Johnson & Powell 1970), the first interstellar detection was reported a few years later (Sinclair et al 1973). Meanwhile, the extension of the known rotational spectrum to higher microwave and millimeter-wave frequencies (Johnson et al 1971;Beers et al 1972) allowed predictions of a large number of unmeasured lines to be made available for interstellar identification of thioformaldehyde .…”
Section: à9mentioning
confidence: 99%